The relationship between leadership style and employee engagement at Permodalan Nasional Berhad (PNB) / Nabila Shafika Roslan - Roslan, Nabila Shafika (Faculty of Business and Management, 2018)
The purpose of this study is to study the relationship between leadership styles towards employee engagement in Permodalan Nasional Berhad (PNB). There are two types of leadership styles which is transformational leadership and transactional leadership. These two types of leadership will measure the most affecting factor towards employee engagement at Permodalan Nasional Berhad (PNB). In this research, the researcher chooses simple random sampling a the method. Consequently, 100 questionnaires were distributed to the employees in Permodalan Nasional Berhad (PNB) and greatly the total returned is also 80. Then, the result of the questionnaire collected was analyzed by using Statistical Package for Social Science (SPSS) 20.0 and were further analyzed using frequency analysis, reliability, regression analysis and descriptive analysis.